2012
DOI: 10.1136/jnnp-2011-301876
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double blind, placebo controlled trial with vitamin D3as an add on treatment to interferon β-1b in patients with multiple sclerosis

Abstract: EudraCT number 2007-001958-99 and ClinicalTrialsGov number NCT01339676.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
204
1
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(219 citation statements)
references
References 35 publications
4
204
1
8
Order By: Relevance
“…That is, vitamin D may decrease inflammation Modern studies of the clinical use of physiological doses of vitamin D are relatively rare (around 5,000 IU/day, see above). At least one RCT of physiological doses shows vitamin D may be clinically helpful as add on treatment in multiple sclerosis, 89 active tuberculosis, 90 rheumatoid arthritis, 91 and lupus, 92 all inflammatory diseases. All clinical treatments decisions are based on a risk/benefit analysis.…”
Section: Discussionmentioning
confidence: 99%
“…That is, vitamin D may decrease inflammation Modern studies of the clinical use of physiological doses of vitamin D are relatively rare (around 5,000 IU/day, see above). At least one RCT of physiological doses shows vitamin D may be clinically helpful as add on treatment in multiple sclerosis, 89 active tuberculosis, 90 rheumatoid arthritis, 91 and lupus, 92 all inflammatory diseases. All clinical treatments decisions are based on a risk/benefit analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, any intervention study of vitamin D in RRMS will have to be an add-on to a conventional immunomodulatory drug with a proven effect on the outcome measures that are relevant for vitamin D. A brief look at observational studies in patients treated with interferons underscores the need for large sample sizes. Thus, one study of 1482 RRMS patients followed for 2 years found lower rates of new MRI activity with increasing 25(OH)D levels, with the lowest rate of new lesions (relative risk = 0.53) for those with 25(OH)D exceeding 100 nmol/l [15]. In another study 25(OH)D was associated with time to relapse or MRI activity in the 97 patients receiving interferon-beta (hazard ratio = 0.58), but not for those 151 receiving glatiramer acetate (hazard ratio = 0.89) [16].…”
Section: Can Vitamin D Reduce Inflammation In Relapsing-remitting Mulmentioning
confidence: 99%
“…Specific deletion of the GM‐CSF receptor on these monocytes, but not on DC, diminished disease severity 39. Multiple sclerosis is associated with VD3 deficiency; its murine model experimental autoimmune encephalomyelitis, and possibly also multiple sclerosis itself, is ameliorated by VD3 supplementation 40, 41. Hence, we speculate that, paralleling the in vitro studies of moDC outlined above, high VD3 conditions in vivo may redirect monocyte differentiation into tolerogenic versus inflammatory DC and contribute to the potential therapeutic effects of such supplementation.…”
Section: Potential Relevance Of Culture Models To Inflammatory (Monocmentioning
confidence: 99%